Influence of Aerobic Oxidation of Mouse Erythrocytes on their Recognition by Macrophages. Issue 3 (June 2000) - Olmos, Gemma; Lotero, L. Alfredo; Herráez, Angel; Alvarez, F. Javier; Murciano, Juan C.; Tejedor, M. Cristina; Díez, José C.
Abstract : Membrane protein modification can change cell surface properties which canbe correlated with altered macrophage-erythrocyte interactions. Mouseerythrocytes were incubated in phosphate buffer for different times toinduce protein modification. Mouse erythrocyte membrane changes wereanalyzed by infrared analyses and gel electrophoresis. Proteolyticdigestion of membrane proteins was observed. After 22 hours preliminaryincubation, the number of erythrocytes adhering to a monolayer ofmacrophages reached a maximum, the majority of which had not beenphagocytosed. Most of the erythrocytes incubated for 40 hours underwentphagocytosis after adhesion to the macrophages.